Ratifikasi Statuta International Criminal Court Dalam Penegakan Hak Asasi Manusia di Indonesia: Perlukah? - B Pongkapadang, Opniel Harsana (IAIN Langsa, 2024)
The prosecution of serious human rights violations in Indonesia is complemented by special courts. These courts are ad hoc and can try cases of past serious human rights violations. By ratifying the Rome Statute, Indonesia will become a state subject to the jurisdiction of the International Criminal Court. However, this feature of subordination is not absolute, but rather complementary. The aim of this research is to determine aspects of serious human rights violations in international law as well as the effectiveness of the implementation of international criminal law in the human rights justice system in Indonesia. The research method is normative law using secondary data with a conceptual approach. The research results show that serious human rights violations in international law can take into account the objectives of international criminal law regulations as well as Indonesian criminal law regulations. These are issues that affect the interests of security, order and peace of the international community and humanity in particular. The International Court of Justice has jurisdiction limited to the most serious crimes of concern to the international community as a whole. Under the Rome Statute, the Court has jurisdiction over serious human rights violations. However, Indonesia has not yet ratified the Rome Statute, due to differing views on how it should function and differing understandings of human rights violations.